The motor insurance industry in South Africa: a survival analysis - Pfukwa, Abbot (My University, 2015)
An interesting phenomenon experienced in the insurance sector is the concept of underwriting cycles. The underwriting cycle challenge usually affects new registered insurers. When the premiums charged in the market are high, above the average, new players are prompted to enter the market and an underwriting cycle commences. New players in the insurance market may threaten the survival of the established companies. Established companies respond by strategically reducing their premiums below the average prices attracting clients by offering a better premium. This chokes the new insurers to death, and once they are out of business and there is less competition, the established insurers, will gradually increase their premiums to maintain profitability. What are the chances of survival of any new player in the short term insurance industry? Are there any significant differences in survival chances of motor insurers to non-motor insurers in the short term insurance sector? Are there any trends in the underwriting profits/losses for insurers who experienced death, years prior to death? Survival analysis methods enable us to answer these questions. We embarked on a survival analysis study, of short term insurance companies in South Africa, over a period of fourteen years. The Kaplan-Meir, test is used extensively in this project. We find that any new registered player in the motor and non-motor insurance industry has over 75% chance of survival over a period of 10 years. There are no significant differences in the survival functions of a motor and a non-motor insurer. Dormancy and fluctuations in net underwriting profits/losses are cited in the trend analysis of insurance companies that experience death
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.